PENGARUH KINERJA KEUANGAN TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL PERUSAHAAN - Sari, Ayu Intan Permata; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
This research is aimed to examine the influence of financial performance to the disclosure corporate social responsibility. The population is manufacturing companies in consumer goods industry sector which are listed in Indonesia Stock Exchange have been selected by using purposive sampling. The data in this research is the financial statements in 2012-2014 periods. 25 companies have been selected as samples. This research has been carried out by using multiple linear regressions analysis and SPSS application.The result of the research shows that: (1) firm size has positive influence to the Disclosure Corporate Social Responsibility, in general large companies will disclose more information than small companies; (2) Profitability does not have any influence to the Disclosure Corporate Social Responsibilty, caused by there is a possibility when a company generates a profit, it will be reprocessed by the company through asset development. (3) Leverage does not have any influence to the Disclosure Corporate Social Responsibilty, because to conduct Disclosure Corporate Social Responsibility does not depend on the level of Leverage, but it is depend on the sensitivity of the company to the social care and their responsibility to the environment.Keywords: Firm size, profitability, leverage, and the disclosure corporate social responsibility